2015
DOI: 10.1371/journal.pone.0133918
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sense of Coherence on Oral Health Behaviors: A Systematic Review

Abstract: ObjectivesThe aim of this review was to critically analyze the empirical evidence on the association between Sense of Coherence (SOC) and oral health behaviors through a systematic approach.MethodsA systematic search up to April 2015 was carried out using the following electronic bibliographic databases: PubMed, Ovid MEDLINE; ISI Web of Science; and Ovid PsychInfo. Studies were included if they evaluated the relationship between SOC and oral health behaviors including tooth cleaning, fluoride usage, dietary ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 39 publications
(173 reference statements)
4
75
1
4
Order By: Relevance
“…According to a salutogenic concept proposed by Antonovsky, sense of coherence (SOC) has recently been established to estimate a person's healthpromoting state (Antonovsky 1980). SOC strongly reflects oral health behaviors, including toothbrushing frequency (Savolainen et al 2009;Elyasi et al 2015). A poor SOC results in psychological problems in early childhood, and is also a powerful predictor for future chronic health problems such as morbid obesity and psychiatric disorders (Raty et al 2005;Honkinen et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a salutogenic concept proposed by Antonovsky, sense of coherence (SOC) has recently been established to estimate a person's healthpromoting state (Antonovsky 1980). SOC strongly reflects oral health behaviors, including toothbrushing frequency (Savolainen et al 2009;Elyasi et al 2015). A poor SOC results in psychological problems in early childhood, and is also a powerful predictor for future chronic health problems such as morbid obesity and psychiatric disorders (Raty et al 2005;Honkinen et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Participants chose from the following five response options: "never," "less than once," "1 time per day," "twice per day," and "three or more times per day." Since twice a day is considered the most suitable frequency for children (Murtomaa 1979;Macgregor et al 1996;Kobayashi et al 2012;Elyasi et al 2015;McKay et al 2016), participants were categorized into two groups: higher toothbrushing frequency group (two or more times per day), and lower brushing frequency group (less than twice per day). In addition to toothbrushing frequency, the presence of dental caries was collected via a self-report questionnaire with the following question: "Do you have any dental caries?"…”
Section: Toothbrushing Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…Disagreement between the reviewers was discussed with M.L. until consensus was achieved (Elyasi et al., ; Hermont et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…In elderly and adult populations, SOC was identified as a psychosocial determinant of oral health-related quality of life [Savolainen et al, 2005a;Boman et al, 2012;Machado et al, 2017], oral health-related behaviors, attitudes towards oral health, knowledge of dental caries [Savolainen et al, 2005b;Bernabé et al, 2009;Lindmark et al, 2011;Elyasi et al, 2015], and dental clinical status [Bernabé et al, 2010[Bernabé et al, , 2012Gupta et al, 2015;Davoglio et al, 2016;Possebon et al, 2017]. Other studies have shown a positive prospective relationship between strong SOC and better oral health-related quality of life among adolescents [Baker et al, 2010;Pakpour et al, 2018].…”
Section: Introductionmentioning
confidence: 99%